Society Recognizes Newly Certified Software Developers. (Computer (00189162), 2008)
The article presents a list of individuals who have passed the IEEE Computer Society Certified Software Development Professional exam and the Certified Software Development Associate exam including Pieter Botman, Bradley Braun, and Michael Buckley.